2020
DOI: 10.1007/s00148-020-00798-y
|View full text |Cite
|
Sign up to set email alerts
|

Children, unhappiness and family finances

Abstract: The common finding of a zero or negative correlation between the presence of children and parental well-being continues to generate research interest. We here consider international data, including well over one million observations on Europeans from eleven years of Eurobarometer surveys, and in the first instance replicate this negative finding, both in the overall data and then for most different marital statuses. Children are expensive: controlling for financial difficulties turns our estimated child coeffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…There is no change in the wave dummies. The significant coefficients on the extended control variables reveal that living with a partner consistently attracts a positive estimated coefficient (and very notably so for loneliness); on the contrary, children are associated with greater levels of depression and anxiety (a not unusual empirical finding: see Blanchflower and Clark, 2021, for a recent contribution). Log income is positive and significant in all of our well-being regressions, with an estimated coefficient that is fairly consistent at around 0.15 (so that doubling monthly income increases well-being by around 0.1 of a standard deviation).…”
Section: Mediationmentioning
confidence: 98%
“…There is no change in the wave dummies. The significant coefficients on the extended control variables reveal that living with a partner consistently attracts a positive estimated coefficient (and very notably so for loneliness); on the contrary, children are associated with greater levels of depression and anxiety (a not unusual empirical finding: see Blanchflower and Clark, 2021, for a recent contribution). Log income is positive and significant in all of our well-being regressions, with an estimated coefficient that is fairly consistent at around 0.15 (so that doubling monthly income increases well-being by around 0.1 of a standard deviation).…”
Section: Mediationmentioning
confidence: 98%
“…It remains puzzling then why many psychologists continue to suggest that well-being is unrelated to age, as it applies to most of the world's population and links to behaviors and outcomes that merit the attention of scholars and policymakers alike. Endnotes 1 We have published papers on the U-shape in well-being for over a period of nearly two decades including Graham (2021, 2020); Blanchflower (2020aBlanchflower ( , 2020bBlanchflower ( , 2020c; Blanchflower and Clark (2020), Oswald (2020, 2019;2009;2008;2004a and2004b;Blanchflower, Oswald and Stewart-Brown, (2013), Bell and Blanchflower (2020) and Graham, C., (2017Graham, C., ( , 2009; Graham, Eggers and Sukhtankar ( 2004); Graham, Laffan and Pinto (2018); Graham and Pettinato (2002) and Graham and Ruiz-Pozuelo (2017).…”
Section: Discussionmentioning
confidence: 99%
“…Helliwell et al (2019) have suggested that the flatter U-shape for the married individuals may come about because "together spouses can better shoulder the extra demands that may exist in mid-life when career and other demands coincide". Our failure to confirm that this is the case for job or time-use satisfaction seems at odds with this hypothesis.10 The Eurobarometer data used byBlanchflower and Clark (2020) also only include information on children living at home. They too cut the sample of parents at age 45.11 Only when we focus on satisfaction with time use do we find that partnered childless men and women report significantly higher satisfaction than partnered men and women with children.12 We also note that overall life satisfaction is lower at higher ages in Eastern and Southern Europe than in Western and Northern Europe, conditional on partnership status and sex.…”
mentioning
confidence: 89%